A CONSTITUENT OF CHAROTAR UNIVERSITY OF SCIENCE AND TECHNOLOGY - Vageriya, Vipin (European Scientific Journal, ESJ, 2014)
â€œA study to assess the effectiveness of Structured teaching Program on knowledge about the prevention of lead poisoning among the mothers of toddlers in selected rural areas of Hassan in Karnatakaâ€.